2023
DOI: 10.3390/ijms24065386
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA as a Diagnostic Tool, Therapeutic Target and Potential Biomarker in Cutaneous Malignant Melanoma Detection—Narrative Review

Abstract: Melanoma is the most serious type of skin cancer, causing a large majority of deaths but accounting for only ~1% of all skin cancer cases. The worldwide incidence of malignant melanoma is increasing, causing a serious socio-economic problem. Melanoma is diagnosed mainly in young and middle-aged people, which distinguishes it from other solid tumors detected mainly in mature people. The early detection of cutaneous malignant melanoma (CMM) remains a priority and it is a key factor limiting mortality. Doctors an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 140 publications
0
4
0
Order By: Relevance
“…In the present study, miR-155 showed significant downregulation in melanoma tissues relative to non-cancer tissues. Considering other coding and noncoding gene panels, this could help in the molecular profiling of this type of cancer, highlighting the potential role of miR-155 as a tissue-based marker that could have insight as a diagnostic molecular marker and future therapeutic target in melanoma, as supported by Poniewierska-Baran and colleagues in their interesting review [ 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, miR-155 showed significant downregulation in melanoma tissues relative to non-cancer tissues. Considering other coding and noncoding gene panels, this could help in the molecular profiling of this type of cancer, highlighting the potential role of miR-155 as a tissue-based marker that could have insight as a diagnostic molecular marker and future therapeutic target in melanoma, as supported by Poniewierska-Baran and colleagues in their interesting review [ 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…MicroRNAs (miRNAs), characterized as small non-coding RNA molecules, play a pivotal role in cellular processes by regulating gene expression and contributing significantly to the modulation of the immune system. In the context of autoinflammatory diseases, the early stages often exhibit distinctive and aberrant miRNA expression patterns, presenting a promising avenue for potential biomarkers (Poniewierska-Baran et al, 2023). The dysregulation of miRNAs not only reflects the complex interplay within inflammatory OPEN ACCESS EDITED BY pathways but also provides valuable insights into the underlying mechanisms of these diseases (Das and Rao, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…NMSCs consist of Basal Cell Carcinoma (BCC), Squamous Cell Carcinoma (SCC), and Bowen’s disease. Both NMSC and MM show a concerning increase in incidence rates [ 1 , 2 ]. In addition to various factors, such as family or personal history, a weakened immune system, and pale skin color, the prevalence of this disease also depends on environmental factors.…”
Section: Introductionmentioning
confidence: 99%